Data from: Minke whales avoid a 15 kHz acoustic deterrent device ... - Boisseau, Oliver (Dryad, 2020)
A controlled exposure experiment was used to determine whether an acoustic deterrent device (ADD) could modify the behaviour of minke whales (Balaenoptera acutorostrata). The Lofitech Seal Scarer emitted a 14.6 kHz tone with a source level of 198 dB re 1 μPa re 1m (rms). During summer 2016, video-range tracking of minke whales was undertaken in Faxaflói Bay, Iceland. After tracking for 30 minutes, the ADD was deployed at 338-1562 m; behaviour was monitored during control, treatment and post-treatment phases. Parameters including dive duration, swimming speed, reoxygenation rate and measures of path predictability were used to quantify responses. In ten deployments, the ADD caused focal animals to move away immediately, typically increasing horizontal speed and directness away from the source and extending subsequent dives. Most whales exhibited sustained movement away after ADD deactivation. Distance of deployment had the largest effect on a multiple regression model. A noise propagation model suggested ... : Times and positions for minke whale surfacings used during data analysis in the manuscript. ...